A narrative analysis of the relationships between the religious perceptions of serious violent offenders and their perception of their punishment - Tihanyi, Miklós (Bogoslovni vestnik, 2025)
This study investigates the characteristics of religiosity among serious violent offenders who actively participate in religious activities in prison and the way that affects their perception of the crime and their sentence. In particular,we examine whether they are remorseful for their actions and desire forgivenessas a part of religious experience. sixteen prisoners in three penitentiaries who had committed serious violent crimes and actively participated in religious events, were interviewed. Analysis of the answers showed a positive correlationbetween a deep, substantive faith experience and acceptance of responsibility.Likewise, faith influences the development of regret for the crime. Those who admit their crime and repent it are motivated by a desire for forgiveness. The religiously sceptical prisoners admit to having committed the crime but do not show remorse. All this suggests that a deep, substantive experience of faith can have a positive impact on the achievement of punishment goals.
Keywords: experiencing punishment; experiencing religiosity; izkušnja kazni; izkušnja religioznosti; izrazito nasilni storilci kaznivih dejanj; kesanje; religious education of prisoners; repentance; seriously violent offenders; versko izobraževanje zapornikov